Diagenesis in tephra-rich sediments from the Lesser Antilles Volcanic Arc: Pore fluid constraints. (1st May 2018) - Murray, Natalie A.; McManus, James; Palmer, Martin R.; Haley, Brian; Manners, Hayley
Abstract: We present sediment pore fluid and sediment solid phase results obtained during IODP Expedition 340 from seven sites located within the Grenada Basin of the southern Lesser Antilles Volcanic Arc region. These sites are generally characterized as being low in organic carbon content and rich in calcium carbonate and volcanogenic material. In addition to the typical reactions related to organic matter diagenesis, pore fluid chemistry indicates that the diagenetic reactions fall within two broad categories; (1) reactions related to chemical exchange with volcanogenic material and (2) reactions related to carbonate dissolution, precipitation, or recrystallization. For locations dominated by reaction with volcanogenic material, these sites exhibit increases in dissolved Ca with coeval decreases in Mg. We interpret this behavior as being driven by sediment-water exchange reactions from the alteration of volcanic material that is dispersed throughout the sediment package, which likely result in formation of Mg-rich secondary authigenic clays. In contrast to this behavior, sediment sequences that exhibit decreases in Ca, Mg, Mn, and Sr with depth suggest that carbonate precipitation is an active diagenetic process affecting solute distributions. The distributions of pore fluid 87 Sr/ 86 Sr reflect these competitive diagenetic reactions between volcanic material and carbonate, which are inferred by the major cation distributions. From one site where we have solid phase 87 Sr/ 86 Sr (site U1396), the carbonate fraction is found to be generally consistent with the contemporaneous seawater isotope values. However, the 87 Sr/ 86 Sr of the non-carbonate fraction ranges from 0.7074 to 0.7052, and these values likely represent a mixture of local arc volcanic sources and trans-Atlantic eolian sources. Even at this site where there is clear evidence for diagenesis of volcanogenic material, carbonate diagenesis appears to buffer pore fluid 87 Sr/ 86 Sr from the larger changes that might be expected given the high abundance of tephra in these sediments. Part of this carbonate buffering, at this site as well as throughout the region, derives from the fact that the Sr concentration in the non-carbonate fraction is generally low (<200 ppm), whereas the carbonate fraction has Sr concentrations approaching ∼1000 ppm.